THE JUSTIFICATION OF SHIA IDEOLOGY IN THE QURANIC HERMENEUTICS: Reading the Interpretation of Nâser Makârem Shîrâzî - Udi Yuliarto; Muhammad Chirzin; Hamim Ilyas (ULUL ALBAB Jurnal Studi Islam, 2023)
This article analyzes the Quranic Hermeneutics according to Nâser Makârem Shîrâzî concerning al-Mahdi theme in al-Amthal Tafseer. He interpreted al-Mahdi’s verses and diverted them to another meaning beyond the text. It is a forced interpretation to fit the desired theme, that Al-Râzî cannot justify, even for a religion’s ideology. A descriptive analytical method using hermeneutic approach on Q.S. al-Anbiya’ [21]:105 is implemented. This approach is applied by textually interpreting the verse followed by an in-depth discussion using ijtihad to justify Shîrâzî’s ideology. Hence, his Quranic Hermeneutics, as associated with Imam al-Mahdi, accommodates two meanings. First, it interprets the Quranic verses textually based on the linguistic principles where no single verse discusses al-Mahdi. Second, conducting an interpretation ijtihad on the verses, referring to the narration of ahl-bayt. He constructs his argument to justify God’s promise regarding the advent of al-Mahdi. Through these steps, he conveys that every Quranic verse contains exoteric (zâhir) and esoteric (bât{in) meanings. Q.S. al-Anbiyâ’ [21]:105 inspires him to perform ta’wîl ijtihadî. The word Zabûr in this verse is confirmed to be the Mazmur verses containing God’s promise, that He will bequeath the earth to the devout people, and tells their characteristics, which are similar to Imam al-Mahdi al-Muntazar’s.